The Effects of Drilling Operation on the Surface Roughness of Modified GFRP Composites - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2018)
The use of fiber reinforced composites with thermoset matrix is widespread in many areas ranging from sports products to multiple industries. This prominence, aside from the lightness of composites, can be attributed to their high mechanical resistance, good corrosion resistance, and strength density ratios that are favorable over their metal counterparts. Although their final states are approached with various single step methods, they often require secondary operations such as turning, milling or drilling. Because composite materials are not homogeneous, machining process may give rise to negative outcomes like the tearing of fibers or damages on the matrix. Composites with thermoset matrix are also brittle materials. Thus, during machining, they are processed by breaking which is not favored for production. Modified glass fiber reinforced composite (GFRP) materials, which are produced with thermoset matrix epoxy resin, are drilled in this study. Previous studies on this field had focused on the processes of turning and milling regarding the products' surface roughness. Therefore, surface roughness of holes, which were drilled according to different parameters by using L 18 matrix prepared with Taguchi's design of experiment on modified GFRP part, having 30% fiber glass, were investigated. This particular study takes on the drilling process which is also essential to manufacturing of the final products of GFRP, in the same framework. In the experiments, the influence of changing spindle speed and feed rate in different drill diameters on the inner surface of the hole, were evaluated using different cutting tools. As a result, the surface roughness of the drill, produced by the uncoated drilling bit with a diameter of 4 mm, spindle speed of 200 rpm and feed rate of 720 mm/min, was determined to be optimal.
Keywords: DELAMINATION; PARAMETERS; DAMAGE